Suppression of the Cassava Mealybug Populations, Phenacoccus manihoti (Hemiptera: Pseudococcidae) By Natural Enemies - Fanani, Muhammad Zainal; Rauf, Aunu; Maryana, Nina; Nurmansyah, Ali; Hindayana, Dadan; Rahayu, Arifah; Setyono, S.; Roestamy, Martin (ASEAN Journal of Science and Engineering, 2024)
The most dominant mealybug species found on cassava is Phenacoccus manihoti. Parasitoid Anagyrus lopezi is a biological agent of P. manihoti in many countries. Monitoring the incidence and population of mealybug and the percentage of parasitization were done, as well as the population of ants and predator insects for 12 consecutive months. The highest incidence and attack rate of mealybugs were 26 and 64%, respectively, during the dry season. A. lopezi was able to suppress the population of P. manihoti between 2-17 individuals per plant with a parasitization rate varied from 12 to 46%. Our study showed that the parasitization rate of A. lopezi increased significantly with the increase in mealybug density. Predators P. ramburi and C. montrouzieri were found in low populations and have not had a significant impact on the mealybug population. Our study demonstrated the important role of natural enemies in suppressing the mealybug population on cassava